Analisis Pengelolaan Sistem Inventori Bahan Baku pada Pabrik Krupuk Raya I dengan Menerapkan Metode Economic Order Quantity (EOQ) - Achtaar, Muhammad Zakki Al; Hidayati, Nur; Arida, Ririn Wahyu (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
One of the main raw materials in the production of uyel crackers at Raya I Factory is tapioca flour. Based on most previous studies, the EOQ method has a function to analyze the inventory of raw materials in the warehouse, including for determining the economic order quantity and also optimizing costs. July to September 2024 is the time for conducting research at Raya I Cracker Factory located in Manisrenggo District, Kediri City. This study analyzed three variables, namely the need for the quantity of tapioca flour raw materials, ordering costs and storage costs. The results of the EOQ method-based study obtained that this business should determine the most economical single order quantity at a volume of 46,188 kg for inventory management in the period October 2023 to September 2024. During this period, Raya I Cracker Factory experienced a decrease in inventory management costs of Rp. 46,212,246.